BLOCKCHAIN TECHNOLOGY FOR SECURING DIGITAL ART OWNERSHIP AND ENHANCING ARTIST AUTHENTICITY RECORDS - Kashid, Pratibha V; Somatkar, Avinash; Guo, Qingchang; Kawale, Sharayu Rinkal; R, Arivukkodi; R, Shanthi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The digital art blistering phenomenon has transformed the manner in which art is produced and contextualized in the art markets in the world, though it has occasioned concerns that border issues of ownership, authenticity and provenance which are horrifyingly questioned. Easy reproduction, editing and re transmission, and proving the authorship and protecting of the artists is difficult in digital art. The provided paper explores the possibility of the blockchain technology being a secure and open method of controlling the ownership of the digital art object and enhancing the authenticity records. Blockchain helps in the creation of verifiable histories of digital assets that cannot be changed and this is done by allowing decentralized ledger keeping, cryptographic hash and smart contracts to be used to create the records. The article also involves the research of blockchain-based systems in particular with the involvement of Non-Fungible Tokens (NFTs) as the embodiment of a unique digital piece of art. It proposes a theoretical model that entails artist registration, tokenization of artwork, ownership tracking, and verifications to ensure the safety of provenance and authenticity. The implementation plan will outline the process of the implementation of a blockchain-based tool, namely, the decentralized storage and the automation of smart contracts, which will allow facilitating an effective transaction and the payment of royalty. Furthermore, a comparison of the advantages of introducing blockchain-based systems over traditional models of art ownership is described in terms of the security, transparency, and accessibility. The paper does list such problems as scalability, regulatory uncertainty and environmental issues, despite these advantages. Based on the findings, it can be concluded that blockchain technology can change the digital art ecosystems which provide a reliable platform of ownership verification and empowering artists, and also emphasize the need to conduct further research and sustainable development.